Women’s Political Participation in Bangladesh in 2008-2018: Status Quo, Obstacles and Future Prospects. - Diana Mutiara Bahari; Favian Dwi Tantra; Risky Fauzi Widodo (Universitas Muhammadiyah Yogyakarta, 2019)
In the contemporary world, the involvement of women in parliament is necessary. However, not all nations uphold the idea of gender equality. Many countries are still trapped by their values and norms such as the patriarchy system. Bangladesh is an example of a country where the patriarchy system has become an obstacle for women to participate in political activities. The current fact has shown its progressivity to involve women in political activities. Therefore, the question arises as of how the future prospect for women in Bangladesh to be able to participate and involve in the political and parliament activities. This study uses the theory of feminism to examine women’s demand that will affect Bangladesh’s future policies on women’s involvement in political activities. This paper will discuss the current condition and the obstacles faced by the women in Bangladesh regarding political activities. Some obstacles such as women dual role, prohibition of women leadership in Islam, absent of women friendly electoral system as well as present negative women psychology of political culture. The method used in this study is a qualitative based research method. This paper concludes demands appears from the women in Bangladesh to increase their involvement in political activities.